The role of saline irrigation of subcutaneous tissue in preventing surgical site complications during cesarean section: A prospective randomized controlled trial - Kanza Gül, Derya (Journal of Surgery and Medicine, 2021)
Aim: Following cesarean section, wound complications develop in 3 to 30% of the patients. The purpose of this study is to evaluate the effect of subcutaneous saline irrigation during caesarean section on postoperative surgical site complications. Methods: This prospective randomized controlled study was conducted between November 17, 2020 and December 16, 2020 at Medipol University, Private Nisa Hospital. A total of 230 women undergoing elective cesarean delivery were divided into 2 groups. The subcutaneous tissue was irrigated with saline solution in group 1 (n=115), and not irrigated in the control group (n=115). On the 7th postoperative day, the surgical site was evaluated for hematoma, seroma, wound dehiscence, and superficial surgical site infection. Results: The incidences of seroma (7% vs. 15.7%, P=0.013), hematoma (6.1% vs. 15.7%, P=0.024) and superficial surgical site infection (4.3% vs. 11.3%, P=0.035) were significantly lower in the saline irrigation group, while the groups were similar in terms of wound dehiscence (P=0.176). Conclusion: Saline irrigation of the subcutaneous tissue during cesarean section decreased the rates of seroma, hematoma, and superficial surgical site infections significantly.